PENDAMPINGAN UMKM KERIPIK DI DESA SUKAKARYA MELALUI PENINGKATAN KEMASAN DAN PEMASARAN ONLINE - Nurhalimah, Siti; Fauzi, Muhammad Rizki; Aphafield, Tresna Ligar; Rahmawati, Ade Siti; Sartika, Dwi; Firdaus, Muhammad; Kharyani, R. Aldini; Amanda, Ressa; Muthiatulmillah, Siti; Fauziah, Siti; Puspahati, Shela (LPPM Universitas Islam 45 Bekasi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving local economic growth, particularly in rural areas. One MSME with significant development potential is “Keripik Si Umi,” located in Sukakarya Village, Bogor Regency. However, this MSME still faces challenges in packaging, labeling, and marketing, which limits its competitiveness in the market. This community service program aimed to provide assistance in improving product packaging, labeling, and online marketing. The implementation methods included an initial observation to identify problems, technical training on packaging and labeling, and direct mentoring in applying digital marketing strategies. The results indicated a significant improvement in packaging quality, shifting from simple LDPE plastic to standing pouch packaging made of polypropylene, which is more appealing and durable. In terms of labeling, the product now meets the standard consumer information requirements. Furthermore, product marketing has successfully expanded through online platforms, increasing market reach. This program concludes that the intervention enhanced the competitiveness of Keripik Si Umi by improving product quality and optimizing marketing, which is expected to contribute to increased sales revenue and sustainable business growth in the long term.